MINAT BELAJAR MENULIS TEKS PROSEDUR SISWA KELAS V SD NEGERI 3 KINTAMANI TAHUN PELAJARAN 2025/2026 - Ni Ketut Marina; I Wayan Numertayasa; Desak Putu Anom Janawati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
A student's learning interest plays a pivotal role in determining their academic achievement, especially when it comes to composing procedural texts at the elementary education level. This research was carried out to examine the level of learning interest among fifth-grade students in writing procedure texts at SD Negeri 3 Kintamani during the 2025/2026 school year, with particular attention given to three core dimensions: attraction to the material, receptiveness, and active participation. A descriptive qualitative design was adopted for this study. The research involved 18 fifth-grade students as the primary participants, while the homeroom teacher acted as a supplementary informant. Data were gathered through in-class observations, semi-structured interviews, and document reviews. The collected information was then processed using an interactive analytical framework that includes data condensation, data display, and verification or conclusion drawing. To ensure the credibility of the findings, triangulation methods were employed. The outcomes indicated that the students' interest in learning to write procedure texts fell into the very good category. Out of the 18 students, 17 exhibited strong levels of interest, receptiveness, and involvement throughout the lessons, whereas only one student continued to need extra support in generating ideas and building self-assurance. Students' interest was encouraged through contextual learning activities, acceptance was reflected in their positive attitudes toward classroom instruction, and engagement was demonstrated by active participation in asking questions, discussing ideas, and completing writing tasks. Furthermore, students' learning interest was influenced by psychological, pedagogical, and learning environmental factors. Therefore, implementing contextual learning, employing varied teaching methods and instructional media, and creating a supportive learning environment contribute positively to improving elementary students' interest in learning to write procedure texts